Modulated structures in the ANNNI model with an external magnetic ﬁeld near criticality - Gonchar, N.S.; Hajduk, H.G. (Condensed Matter Physics, 1999)
Conditions for a phase transition from the paramagnetic state to the modulated structure are found in a class of anisotropic Ising models with an external magnetic ﬁeld. The critical value of the external magnetic ﬁeld is obtained. Branching equations are derived and small branching theorems are proven for commensurate and incommensurate conﬁgurations.